Rancangan Saluran Pada Pemindahan Aliran Sungai Kili Besar Di Area Pertambangan Batubara di Lahat, Sumatra Selatan Menggunakan Apllikasi HEC-HMS dan HEC-RAS - Mendrofa, Yudha Chrisman; Tedy Agung Cahyadi,; Shofa Rijalul Haq, (ReTII, 2023)
In coal mining, it is common to find a river flowing across the mining area. This certainly affects production and mining operations, so special treatment needs to be carried out, namely moving river flows. When transferring river flow, it is necessary to pay attention to several things, such as the design river discharge, dimensions of the new river channel, and so on. This is done without damaging the environment and does not result in future flooding in the new river channel. Using the HEC-HMS and HEC-RAS applications can help in channel calculations and modeling